2020
DOI: 10.1039/c9sc05623h
|View full text |Cite
|
Sign up to set email alerts
|

A robust photoluminescence screening assay identifies uracil-DNA glycosylase inhibitors against prostate cancer

Abstract: The discovery of UDG inhibitors against prostate cancer by using a robust photoluminescence screening assay that can avoid false negatives arising from the background fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…[17][18][19] The MS and HPLC methods have high backgrounds resulting from articial DNA damage during complex sample preparation. 20,21 Alternatively, several new methods, including colorimetric, 22 electrochemical, 23 uorescent, 10,15,24,25 and luminescent assays, [26][27][28] have been developed. The colorimetric assay enables the visualized detection of hOGG1 activity, 22 but the preparation of DNA-AuNP probes is timeconsuming and laborious.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] The MS and HPLC methods have high backgrounds resulting from articial DNA damage during complex sample preparation. 20,21 Alternatively, several new methods, including colorimetric, 22 electrochemical, 23 uorescent, 10,15,24,25 and luminescent assays, [26][27][28] have been developed. The colorimetric assay enables the visualized detection of hOGG1 activity, 22 but the preparation of DNA-AuNP probes is timeconsuming and laborious.…”
Section: Introductionmentioning
confidence: 99%
“…The uorescent assay utilizes 8-oxoG repair-induced assembly of a quantum dot-based nanosensor to detect hOGG1 activity, 10 but the intricate probe modications and costly uorescent nanomaterials limit its wide application. The luminescent assays based on the combination of DNA repair-response cleavage with the G-quadruplex-selective iridium(III) complex 26,28 and in vitro green uorescent protein expression 27 enable the detection of DNA repair enzyme activity 26 and inhibitor screening, 27,28 with distinct advantages of easy probe preparation, simple strategy, and low cost compared with the uorescent assays. However, due to the lack of target amplication, the improvement in sensitivity is not signicant for luminescent assays.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the ability of 1 to target Keap1 and Nrf2 in cellulo , the cellular thermal shift assay (CETSA) was conducted ( Fig. 3 A) [ 83 , 84 ]. Complex 1 significantly stabilized Keap1 and shifted the Keap1 melting curve by ca.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, virtual screening has been employed for identifying inhibitors of cancer targets ( Zhong et al, 2016 ; Li et al, 2020 ). For example, Russo Spena et al (2019) identified VS10 as a selective PIN1 inhibitor with anti-ovarian cancer activity through virtual screening.…”
Section: Introductionmentioning
confidence: 99%